ANALISIS RASIO KEUANGAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG LISTED DI BURSA EFEK INDONESIA - Nusbantoro, Ariwan Joko (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2011)
This research aims to examine the effect of Current Ratio, Debt to Equity Ratio, Inventory Turnover, and Total Assets Turnover to Return on Equity of Food and Beverage companies, Listed on Indonesian Stock Exchange. The data were data from 2003 to 2008, containing a sample of 15 companies. A purposive sampling method was employed generating a total of 63 observations. Multiple Linear Regression Analysis is used to test hypotheses. The Results show that Current Ratio, Inventory Turnover, and Total Assets Turnover are significantly influenced Return on Equity leading to accept the proposed hypotheses. Debt to Equity Ratio has negative and significant influence on return on equity but it was in opposite direction. Keywords: Current Ratio or Working Capital Ratio, Debt to Equity Ratio, Inventory Turnover, Total Assets Turnover, and Return on Equity.